2017
DOI: 10.1590/1413-81232017224.26862016
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdades regionais na saúde: mudanças observadas no Brasil de 2000 a 2016

Abstract: Advances in reducing poverty and inequalities in the 2000s had a paradoxical effect in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
102

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 216 publications
(185 citation statements)
references
References 6 publications
3
80
0
102
Order By: Relevance
“…The Brazilian authors state that the RAS proposal reflects in the recent alignment in the health policy in the Country with International reforms of the universal systems and that the deployment of the RAS has accompanied a different rhythm of the regionalization. 2 The contribution made by integrating different levels in health care was also confirmed by a study in Denmark, 24 highlighting that the regions and the cities have implemented various initiatives, such as the Pathway programs for chronic diseases, which promotes integrated care. Unfortunately, our study identified that the regionalization did not result a fully regionalized primary care.…”
Section: S92mentioning
confidence: 83%
See 2 more Smart Citations
“…The Brazilian authors state that the RAS proposal reflects in the recent alignment in the health policy in the Country with International reforms of the universal systems and that the deployment of the RAS has accompanied a different rhythm of the regionalization. 2 The contribution made by integrating different levels in health care was also confirmed by a study in Denmark, 24 highlighting that the regions and the cities have implemented various initiatives, such as the Pathway programs for chronic diseases, which promotes integrated care. Unfortunately, our study identified that the regionalization did not result a fully regionalized primary care.…”
Section: S92mentioning
confidence: 83%
“…However, the concentration of cities with higher rates of poverty remains in the North and Northeast regions in the country. 1 Albuquerque et al 2 reported that the regional policies in health assisted in advances to minimize these inequalities through the prioritization of regional strategies intergovernmental organizations and the development of health care services. Other authors reinforce that the regionalization process could be much more developed if there was a better appropriation of territory complexities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 On the other hand, the evidence to the division of established responsibilities among the sub-national governments in the process of decentralizing SUS and the relevance of the States in the provision of services is more complex in regions with lower economic development. 7 In the research, it draws attention to the importance of the private sector in the provision of outpatient services and very high hospital expenditures, which indicate its tendency to work in care segments are more well-paid and valued by buyers of the S116 Lima LD et al…”
Section: Discussionmentioning
confidence: 99%
“…Although, income improvements and capacity offering had occurred in 2000 to 2016, the socioeconomic differences and the composition in the health services among regions constituted for purposes to plan and manage the intergovernmental in SUS (designated as 'health areas') are quite significant. 23 The article was guided by the following question: How does the governance of specialized assistance in health regions configure? It is assumed that different arrangements of governance in SUS are associated to managers' distribution of responsibilities in the provision of services and the expenditures on specialized assistance by public agents (governmental entities/spheres) and private (profitable or not) with greater or lesser regional concentration in the pole cities.…”
Section: Introductionmentioning
confidence: 99%